Message received : 7 steps to break down communication barriers at work - Donohue, Mary E. (McGraw-Hill, 2021)
"From a TEDX speaker with nearly half a million views and renowned digital psychologist, an action plan for driving creativity and innovation among generationally diverse staff in today's technology-heavy workplace Each generation in the workforce today-Baby Boomers, GenX, Millennials, and GenZ-responds differently to different styles of leadership and communication. Message Received provides an actionable plan that readers can use to optimize communication within departments and among teams. Author Mary Donohue delivers a 7-step solution for motivating and inspiring people who respond to communication approaches differently, especially when it comes to technology: Step 1: Understand how the human brain responds to communication through technologyStep 2: Identify how you listenStep 3: Diagnose team engagement issuesStep 4: Customize conversation Step 5: Analyze your team's Digital EQ Step 6: Interpret generational triggersStep 7: Mastery: Realizing your power as a communicator Instead of feeling unheard, frustrated, and held back because of different communication preferences, Message Receivedprovides the tools you need to increase staff engagement and productivity. Through case studies, evolutionary communication science, evidence-backed research, and more, readers will walk away with the tools they need to be their most influential-self"--